Response efficacy of PD-1 and PD-L1 inhibitors in salivary gland cancers: a systematic review and meta-analysis - Babamohamadi, Zahra; Taherkhani, Amirreza; Yousefzadeh, Ali; Moradi, Ali; Heidari, Marziyeh; Hoseini Nasab, Zahra Sadat; Haghi, Seyedeh Mona; Afkhami, Ayda; Belbasi, Mohaddeseh; Noroozi, Masoud; Deravi, Niloofar (Frontiers in Oncology, 2025)
BackgroundSalivary gland carcinoma (SGC) is an infrequent malignancy characterized by various pathological subtypes. Immune checkpoint inhibitors (ICIs) have emerged as promising therapeutic strategies for several cancers. Evidence suggests that ICIs may be effective against rare neoplasms, including SGC. This meta-analysis evaluated the efficacy of programmed death-1 (PD-1) and programmed death ligand 1 (PD-L1) inhibitors in treating salivary gland cancers.MethodA thorough search was conducted in PubMed, Scopus, and Google Scholar databases up to 24 February 2024. The title, abstract, and full text of related articles were extracted and screened, and the quality of the included articles was assessed. The data extracted were then analyzed. The research protocol of this systematic review and meta-analysis was registered on the PROSPERO website.ResultsAltogether, a total of five cohort studies and three randomized controlled trials (RCTs) with a total population of 532 were included in these meta-analyses. These studies were conducted in the USA, Japan, France, and China. The average age of the patients was between 53 and 67 years. Our analyses showed an increase in progression-free survival in the cohort studies and RCTs, and the pooled effect is 1.12 (95% CI 1–1.25) and 1.14 (95% CI 1.07–1.20), respectively, in patients with SGC who received PD-1 and PD-L1 inhibitors.ConclusionThis meta-analysis suggests that PD-1 and PD-L1 inhibitors in patients with salivary gland cancer can significantly increase progression-free survival. Due to the high heterogeneity of the studies, more RCTs with a larger sample size are required to prove the association.